Evaluation of Pumping HR (Human Resources) Model-Based Training Program on Human Resources Development at Bogor Agricultural University (IPB) - Amir Tengku Ramly (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
The evaluation study of pumping HR model-based HRD training program at Institut Pertanian Bogor (IPB) is a program evaluation to see the program effectiveness against the professionalism and performance of employees. This research is evaluative research with a model frame of CIPP of Stufflebeam, with evaluation components: context, input, process, and product. Pumping HR model-based HRD training program at IPB is a beneficial program for employment and personal, which have an impact on performance. Considering the context, this program supports the goal of Human Resource Development of IPB. Considering the input, this program is designed tailored to the need of Human Resource in IPB to (1) reinforcement of the values and beliefs, (2) strengthen competence, and (3) encourage successful behavior in terms of responsibility, professionalism, and friendliness in working. Considering the process, this program is preferred and fun for participants and considering the product (output and outcome) this program provides benefits and clear impacts for the performance of the employee.